2022
DOI: 10.1007/s10875-022-01380-9
|View full text |Cite
|
Sign up to set email alerts
|

Hypoparathyroidism-Retardation-Dysmorphism Syndrome due to a Variant in the Tubulin-Specific Chaperone E Gene as a Cause of Combined Immune Deficiency

Abstract: Background Hypoparathyroidism-retardation-dysmorphism (HRD) syndrome is a disease composed of hypoparathyroidism, growth retardation, severe developmental delay, and typical dysmorphic features caused by the tubulin-specific chaperone E gene variant. Many patients succumb in infancy to HRD due to overwhelming infections mainly caused by Pneumococcus spp. Knowledge related to the immune system in these patients is scarce. Purpose To define the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Only six studies were made within multi-countries (n = 6) [ 10 , 33 , 35 , 51 , 95 , 132 ]. The majority of the studies were single centre [ 4 6 , 8 , 9 , 19 , 25 32 , 34 , 37 39 , 41 , 43 47 , 49 , 50 , 52 60 , 62 , 64 , 66 69 , 71 , 72 , 75 80 , 82 84 , 86 90 , 93 , 94 , 96 , 98 – 117 , 119 131 ] and only 23 studies were multi-centre [ 7 , 10 , 33 , 35 , 36 , 40 , 42 , 48 , 51 , 61 , 63 , 65 , 70 , 73 , 74 , 81 , 85 , 91 , 92 , 95 , 97 , 118 , 132 ]. Among all included studies in our systematic review, only one study reported on the other potential modifiers in immunity-related pathways for all diagnosed IEIs in children who were infected with SARS-CoV-2 (n = 1, 0.9%) […”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only six studies were made within multi-countries (n = 6) [ 10 , 33 , 35 , 51 , 95 , 132 ]. The majority of the studies were single centre [ 4 6 , 8 , 9 , 19 , 25 32 , 34 , 37 39 , 41 , 43 47 , 49 , 50 , 52 60 , 62 , 64 , 66 69 , 71 , 72 , 75 80 , 82 84 , 86 90 , 93 , 94 , 96 , 98 – 117 , 119 131 ] and only 23 studies were multi-centre [ 7 , 10 , 33 , 35 , 36 , 40 , 42 , 48 , 51 , 61 , 63 , 65 , 70 , 73 , 74 , 81 , 85 , 91 , 92 , 95 , 97 , 118 , 132 ]. Among all included studies in our systematic review, only one study reported on the other potential modifiers in immunity-related pathways for all diagnosed IEIs in children who were infected with SARS-CoV-2 (n = 1, 0.9%) […”
Section: Resultsmentioning
confidence: 99%
“…Among them, 40 have DiGeorge syndromes (31.7% of all syndromic combined immunodeficiencies) [ 46 , 56 , 63 , 65 , 81 , 92 , 95 , 97 , 108 ], 25 have immunodeficiency with ataxia-telangiectasia (19.8%) [ 34 , 46 , 48 , 52 , 62 64 , 73 , 74 , 81 , 97 , 108 , 117 , 118 , 124 ], and 14 have Wiskott-Aldrich syndromes (WAS) (11.1%) [ 5 , 40 , 46 , 48 , 63 , 65 , 81 , 95 , 99 , 124 ]. The remaining 47 patients have Nijmegen breakage syndromes (n = 9) [ 81 , 108 ]; immunodeficiencies with centromeric instability and facial anomalies (n = 6) [ 19 , 34 , 48 , 73 ]; ARPC1B deficiency (n = 3) [ 39 , 40 , 95 ]; STIM1 deficiencies (n = 2) [ 34 , 74 ]; anhidrotic ectodermodysplasia with immunodeficiency caused by hypomorphic mutations in encoding the nuclear factor κB essential modulator (NEMO) protein (n = 2) [ 30 , 73 ]; hypoparathyroidism-retardation-dysmorphism syndromes (n = 3) [ 47 ]; MCM4 deficiencies (n = 2) [ 62 ]; Kabuki syndrome (n = 2) [ 63 , 108 ]; PGM3 deficiency (n = 2) [ 76 , 95 ]; ORAI-1 deficiency (n = 1) [ 125 ]; TBX1 deficiency (n = 1) [ 19 ]; Bloom syndrome (n = 1) [ 46 ]; Schimke immuno-osseous dysplasia (n = 1) [ 46 ]; unspecified hyper IgM syn...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations